Pengaruh Jenis Kayu dan Jumlah Lapisan Terhadap Sifat Venir Lamina - Mochamad Isa Iskandar; Achmad Supriadi (Jurnal Ilmu Pertanian Indonesia, 2017)
This study aims to determine the effect of wood species and the number of layers of veneer against laminated veneer properties. Wood species consist of sengon, pine, and mixed pine sengon. Laminated veener made by a number of layers consist of 4, 6, and 8 layers. The difference of a number of layers was to identify quality of laminated veneer. The adhesive used is urea formaldehyde (UF) liquid. The results showed that the average moisture content of 10.76%, density of 0.54 g/cm3, delamination 5.8%, MOE 124.108 kg/cm2, and MOR 450.74 kg/cm2. The moisture content and delamination made all meet the Indonesian National Standard. Statistically, wood species were a significant effect on moisture content, density, MOE, and MOR, while various of layers were a significant effect on moisture content, density, delamination, MOE, and MOR. The number of layer’s laminated veneer made higher of water content, density, delamination, and MOR.